New dextrin nanomagnetogels: production, characterization and in vivo performance as dual modality imaging bioprobe - Gonçalves, Catarina (2014)
Dual modality contrast agents, such as radiolabelle d magnetic nanoparticles, are promising candidates for a number of diagnostic applications, since they combine two complementing imaging modalities, namely photon emission computed tomography (SPECT) and magnetic resonance imaging (MRI). The benefit of such combin ation lies on the ability to interpret more accurately abnormalities in vivo , by integrating the high sensitivity of SPECT with the superb spatial resolution and anatomical information provi ded by MRI [1]. Superparamagnetic iron oxide nanoparticles (SPION) have been extensively s tudied as MRI contrast agents [2]. SPIONs need to be coated in order to allow formulation in aqueous solutions and to increase in vivo stability [3]. Dextrin nanomagnetogels consists on superparamagnet ic iron oxide nanoparticles ( γ -Fe 2 O 3 ) stabilized within hydrophobized-dextrin nanogel (sc heme 1). The nanomagnetogel formulation, with about 4 mM of iron and a diameter of 100 nm, p resents relevant features such as superparamagnetic behaviour, high stability, narrow size distribution and potential for magnetic guidance to target areas by means of an external ma gnetic field [4]. The functionalization of the dextrin nanomagnetogel with a DOTA-monoamide ω -thiol metal chelator and radiolabelling with 111 In were used to ascertain its in vivo stability and behavior (blood clearance rate and o rgan distribution) after intravenous administration in m ice model. The surface modification of the nanomagnetogel with PEG 5,000 was accomplished in a n attempt to escape the phagocytic system. The unloaded radiolabeled dextrin nanogel ( around 30 nm) showed lower uptake in the liver, spleen and kidneys than the nanomagnetogel l oaded with SPIONs (around 110 nm). This difference in biodistribution profile can be ascrib ed to the differences in the particle size. Nanomagnetogel pegylation resulted in lower liver a nd spleen accumulation. The blood half-life obtained was approximately 4 hours for all formulat ions. A good correlation between the amount of polymer (quantified through radioactivity) and t he amount of iron (ICP measurement) in the spleen was observed, indicating that leakage of iro n from the nanomagnetogels after intravenous administration was negligible. The pilo t imaging study demonstrated good performance of dextrin nanomagnetogels as dual moda lity imaging (MRI and SPECT) bioprobes as expected by the high transverse relaxi vity (215-248 mM -1 s -1 ) obtained in vitro , higher than those of commercial available formulati ons (160-177 mM -1 s -1 ). The production of the nanomagnetogel is simple and easy to scale up, thus offering great technological potential.